1997
DOI: 10.1016/s0008-6363(97)00049-7
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular angiotensin converting enzyme activity and expression is increased during hypoxic pulmonary hypertension

Abstract: Chronic hypoxia has a differential effect on left and right ventricular ACE activity and that the sites of altered ACE expression are highly localized. We speculate that locally increased right ventricular ACE activity and expression may play a role in the pathogenesis of right ventricular hypertrophy secondary to hypoxic pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 33 publications
2
37
1
1
Order By: Relevance
“…Two weeks of HH exposure increased mean pulmonary arterial pressure and total pulmonary resistance, confirming PH. In addition, 2 wk of HH significantly decreased stroke volume and increased RV and right atrial pressures (summarized in Table 1), confirming concomitant RV dysfunction, as previously observed in this model (24,28).…”
Section: Resultssupporting
confidence: 87%
“…Two weeks of HH exposure increased mean pulmonary arterial pressure and total pulmonary resistance, confirming PH. In addition, 2 wk of HH significantly decreased stroke volume and increased RV and right atrial pressures (summarized in Table 1), confirming concomitant RV dysfunction, as previously observed in this model (24,28).…”
Section: Resultssupporting
confidence: 87%
“…2), indicating a stimulating effect of hypoxia on both AT 1 expression and receptor density in VSM cells. Chronic systemic hypoxia has been shown to activate RAS in a number of tissues, including the kidney, lung, heart, and pancreas (11,29,34). Leung et al (24) also recently reported an upregulation of AT 1 receptor expression and function in the carotid body by isobaric hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ACE activity and expression in the RV have been reported during chronic hypoxia (25). In addition, the benefit of ACE inhibitors and AT 1 receptor antagonists against the development of RV hypertrophy (13,14,26,32,41) point for an important role of ANG II in the process.…”
Section: Discussionmentioning
confidence: 99%